2021
DOI: 10.1097/aud.0000000000001146
|View full text |Cite
|
Sign up to set email alerts
|

Using Narrow Band CE-Chirps to Elicit Cervical Vestibular Evoked Myogenic Potentials

Abstract: Objectives: To compare the effects of Narrow band CE-Chirps (NB CE-Chirps) and tone bursts (TBs) at 500 Hz and 1000 Hz on the amplitudes and latencies in cervical vestibular evoked myogenic potentials (cVEMPs).Design: Thirty-one healthy adult volunteers of varying ages were tested by air conduction at 95 dB nHL. Recording conditions were randomized for each participant and each modality was tested twice.Results: NB CE-Chirps showed larger corrected amplitudes than TBs at 500 Hz (p < 0.001) which were themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…On contrary, Reddy et al 15 revealed significantly larger cVEMP amplitude responses for 500 Hz NB CE-chirps than broadband chirps, clicks, and 500Hz tone bursts. In contrast to tone bursts, Mat et al 14 also reported similar findings for 500Hz and 1000Hz NB CE-chirp stimulations. Despite the fact that the study was the first of its kind to compare multifrequency NB CE chirps and tone bursts, it was restricted to only two frequencies.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
See 4 more Smart Citations
“…On contrary, Reddy et al 15 revealed significantly larger cVEMP amplitude responses for 500 Hz NB CE-chirps than broadband chirps, clicks, and 500Hz tone bursts. In contrast to tone bursts, Mat et al 14 also reported similar findings for 500Hz and 1000Hz NB CE-chirp stimulations. Despite the fact that the study was the first of its kind to compare multifrequency NB CE chirps and tone bursts, it was restricted to only two frequencies.…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…12 Soon enough these NB CE-chirps have found their way into being effective stimuli in eliciting cVEMPs. 8,14,15 There has been no disagreement among the studies about the shorter latencies of cVEMPs for the chirp than tone bursts. 8,14,15,24 However, the amplitude of NB CE-chirp evoked VEMPs remain equivocal as several researchers have reported significantly higher amplitude responses than tone bursts 14,15,24 while others have rejected the claim.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations